Sound Governance dan Gerakan Antikorupsi - Augustin Rina Herawati; Tri Yuniningsih; Endang Larasati (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
The current rampant practice of corruption with various modus operandi has caused the Government to make efforts to prevent and eradicate it by issuing Law Number 31 of 1999 concerning the Eradication of Corruption Crimes through the concept of sound governance. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques which refers to sources available both online and offline. The results of the study concluded that sound governance as a preventive instrument against acts of corruption, the concept of sound governance can be used as an indicator of testing an action by government officials. Efforts to prevent acts of maladministration must be carried out using sound governance principles in an effort to eradicate corruption by government administration. The abuse of authority is an act of maladministration caused by actions that are not based on the principle of good administration in the form of the principle of prohibition of acting arbitrarily, the principle of justice, the principle of legal certainty, the principle of trust, the principle of equality, the principle of proportionality, the principle of prudence caution and considerations. Based on the eight principles of sound governance, the government apparatus will perform the duties and functions of government by always paying attention to these principles to become an effort to eradicate corrupt.